Development of interactive UiTM residential college information kiosk / Norfaiza Abdullah - Abdullah, Norfaiza (2005)
Nowadays, multimedia has shown rapid changes and has positive impact on delivering the infomnation. Recently, many people use multimedia application in their life whether to entertain themselves, to study or as the references. Therefore, many multimedia companies take this opportunity to sell their product either on CD-Rom, online or kiosk based multimedia. An infomnation kiosk is a public stand that supplies text, graphics, video, animation and sound infomnation to the user. The application is an interactive multimedia program which can run on a local computer or via an intranet connection within the enclosure. This project is focusing on the infonnational kiosk which is the presentation will display more on specific on the information of UiTM Residential College. Since there are quite a few constraints with the traditional method, therefore, this project is canied out to develop multimedia presentation of UiTM Residential College that could be a reference to students as well as the visitors. The data related to the project have been collected through the internet, observation, reading and interviewing. However, for a given limited time, only one residential college had been chosen to be completed with the kiosk application that is located at Kolej Melati. This project found that the kiosk application is able to reduce time on getting information and facilitate officer's work